The concept “Russian” in the conceptosphere of Alexander Bashlachov - Маслий, Елена Васильевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
In the work of the famous Russian rock bard A. Bashlachov, the synthesis of the borrowed western musical and poetic forms and the Russian national tradition was completed. This author's texts are created in the genre of “literary poetry”, which differs from “song poetry”with its classical poetic form and content. Despite the small amount of the creative heritage of this author (about 80 verses in all), he demonstrates the depth of penetration into the philosophical and moral essence of the Russian life.The article is devoted to the description of the concept “Russian” in the conceptual sphere of A. Bashlachov. It is established that the nucleus of the concept is formed around the meanings of ‘love’ (‘heart power’), ‘pain’, ‘soul’, ‘material and spiritual poverty’, ‘trials’. The close periphery of the concept defines a whole range of characteristics: death as a measure of life, aspiration to heaven, cruelty, duality, propensity to extremes, grief-melancholy, passion, thirst for a miracle, craving for considerable, moral promiscuity, lack of reflection and others.